Solving The Students’ Problems In Writing Narrative Essay Through Pentigraf Writing Technique - Novi Rahmania Aquariza; Tatik Muflihah (CV. Kalimasada Group Profesional, 2023)
This study looks into how an English lecturer used the Pentigraf writing technique to teach writing during the second semester of English pre-service lecturers. The employment of the Pentigraf writing approach by the English lecturer and the students' perceptions of it were the subjects of a narrative inquiry, which was chosen as the research design. The study's findings show that: 1) The professor employs Pentigraf writing because it is straightforward, entertaining, and efficient. 2) The preservice lecturer's poor language competence was the biggest issue the lecturer faced when employing the Pentigraf writing approach. 3) Before implementing the Pentigraf writing approach, teaching materials must be prepared. 4)Students in classes three and four demonstrated positive attitudes toward the Pentigraf writing style by acknowledging that it made writing easier for them to learn, motivated them more, and made it more pleasant. This study's implications are meant to aid in the development of writing instruction methods.